Archival documents on repressions in the Osoaviakhim of the Uzbek SSR (1937-1939) - Shamsitdinov Ravshan Rustambekovich (Genius Publishing Group, 2023)
As you know, documents are one of the foundations for the study of the history of a particular period of society and the state. The study of the most tragic period in the history of Soviet power, when mass repressions were carried out, especially during the period of the Great Terror, without archival documents is unthinkable. The official documents of the party and Soviet organs of the USSR, including those of the Uzbek SSR, play a huge role in the analysis of the essence and monstrous consequences of political repression in the USSR, especially in 1937-1938. Among them, the documents from the archives of the NKVD (People's Commissariat for Internal Affairs) of the USSR, both central, republican and peripheral ones provide a huge mass of information about the organization and conduct of repressions against their own people. The activities of punitive bodies, the sad fate of over 1.5 million arrested people, of whom about 700,000 were shot. The article provides materials from the archives of the State Security Service (SSS) of the Republic of Uzbekistan on the case of Osoaviakhim1 (Society of Assistance to Defense and Aviation Chemical Construction of the USSR) of the Uzbek SSR, whose leaders and workers were repressed in those terrible years of Soviet rule in Uzbekistan
Keywords: Osoaviakhim; anti-Soviet; sabotage; counterrevolution